The Strategy at Improving of Balinese Women Representation in the Legislature - Sukiada, I Nyoman (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
Since the reform era, the legislator position commonly was contested. The various legislation has been established to improve the women representation in the legislature. Although, the quota of 30% was not reached as women representation target in Bali province, however, the legislator position was contested by the women should be appreciated as an effort to accelerate a gender equality in the politic. The research was intended at understanding and describing a more precise strategy for the women struggle in the future. The critical theory and the method of qualitative descriptive were used in the present study that was conducted in Bali province. The data was obtained was done through an observation, interview, and library studies. The results of the research were to increase the women representation in the legislature could be done through various strategies. First, improving Balinese womens education; second, improving Bali womens political participation; third, improving Balinese women independence in the economy sector; fourth, holding broader social networking.